A rigorous multipolar framework for nanoparticles optical properties description : theory and experiments - Rouxel, Jeremy (2016)
Using metallic nanoparticles with a threefold symmetry thorough the study, the impact of the symmetry on the nonlinear properties is investigated. Interpretations of polarization-resolved SHG experiments indicate the importance of multipolar resonances, in particular quadrupole and octupole, to explain the strong values of the nonlinear susceptibilities in such systems. A fully irreducible formalism is then developed to treat extended objects like nanoparticles. In this formalism, the nonlinear response tensor is a discrete set of values easily constrained by symmetries instead of a field. This formalism permits to describe simply linear and nonlinear optical response from nanoparticles. Finally, time-domain experiments are conducted with the aim to connect spatial and spectral properties. These experiments allow to interpret the spectra in terms of eigen-modes.